Penerapan Teknologi Location Based Service (LBS) Untuk Menemukan Layanan Kesehatan Terdekat Berbasis Android - Taufiqur Rohman, Abid; Yanti, Marita Dwi; Maulana, Haisyam (Jurnal Sistem Informasi Galuh, 2024)
Health services are a series of actions and services aimed at maintaining, restoring, or improving the health of individuals and the community, organized by institutions such as hospitals, health centers, clinics, pharmacies, and other health facilities. The nearest health service search application using the Location Based Service (LBS) method, as an innovative solution, is here to facilitate users in finding health services with efficiency. The purpose of using the Location Based Service (LBS) method in the development of the nearest health service search application is to improve the accuracy and personalization of services presented to users. The development of this application then involves the stages of planning, needs analysis, design, implementation, testing, and maintenance using the Software Development Life Cycle (SDLC) approach. Through black box testing, the development of the nearest health service search application using the Location Based Service (LBS) method has given positive results. The LBS method proved its superiority in providing accurate location access, real-time navigation integration, search efficiency, provision of relevant recommendations, and increased accessibility of health information. The main functionality of the application, including location search for hospitals, health centers, pharmacies, maternity hospitals, and clinical laboratories, was verified to run well without significant bugs.